CHRYSANTHEMUM FLOWERS AS A SOURCE OF IDEAS FOR CREATING PARTY WEAR - Suryani, Adelia; Suhartini, Ratna (Universitas Negeri Yogyakarta, 2024)
Chrysanthemums have several types of flowers with attractive petal shapes and colours. This research describes the making process and the result of men's and women's party wear with chrysanthemums as decorative trims. This research method uses a double-diamond design process consisting of four stages: discovered, defined, developed, and delivered. The discovery stage is the stage of finding the source of ideas as outlined in the mood board, inspired by the arrangement of petals and varied colours in flowers. The defined stage was to create eight designs of women's party wear and four designs of men's party wear based on the mood board. In the development stage, the women's party fashion will be created using the draping technique on a medium-sized mannequin, and the men's party wear will be created using a large-size construction pattern. The deliver stage is the stage of making decorative trims in the form of chrysanthemum flowers and fabric manipulation tucking as the centre of attention on the apparel. The result of the research was a party dress that was based on the source of the chrysanthemum flower idea. Recommendations for future research can explore the application of chrysanthemum flower idea sources on different designs.